An 80.4% peak power efficiency adaptive supply class H power amplifier for audio applications - Zhang, Xiang (2021)
This paper presents a novel class H power amplifier aiming for audio applications on battery-powered electronic devices. The power supply of the amplifier is adaptively adjusted to track the instantaneous input signal amplitude for higher power efficiency. By embedding audio input signal amplitude information into the class AB amplifier's output common-mode voltage level, the amplifier is able to operate with only single-rail power supply and demonstrates more smooth transitions between the light load and heavy load mode, hence achieves lower total harmonic distortion (THD) for a wide load range. Fabricated in the AMS 0.18-μm CMOS process, the chip consumes 3.52 mW quiescent power and is able to deliver 526 mW peak output power to a 16 Ω load. The measurement results indicate that the amplifier incurs no deterioration on THD when entering the supplytracking mode and achieves a lowest THD+N ratio of -80 dB. The peak power efficiency of the system is 80.4%; moreover, it demonstrates significant higher efficiency for medium load range compared to other linear mode amplifiers.